Rat-running through Walmer Estate, University Estate and Upper Woodstock during the PM peak period - Tarrant, Adrian Joshua (Department of Civil Engineering, 2016)
Urban sprawl remains as a remnant of previous Apartheid legacy policies and has a daily impact on the majority of South African commuters: large, densely populated residential areas (i.e. informal settlements) are generally located on the periphery of towns or cities, far away from areas of employment. As a result, a large number of commuters have to travel great distances to-and from work on a daily basis, and those making use of private vehicles have to accept very high levels of congestion for a large part of their journey. Certain motorists, therefore, carefully select routes, in an attempt to bypass some of this congestion experienced on the arterials and highways, to minimise their travel time and many times this is achieved through the practice of rat-running. This minor dissertation proposes to quantify the number of rat-runners and to identify the routes that the motorists use when moving through a pre-defined study area, with a view towards developing an effective solution to this problem. To achieve this, it is necessary to explore the root causes behind rat-running and investigate what has been done elsewhere to, successfully, mitigate this problem. This information was used to derive a number of proposed mitigating measure alternatives, applicable to the study area's current rat-running where, after a final decision, a preferred solution and the way forward was established. Problem Description The existing Cape Town CBD is positioned in a unique location: the topography of the City, i.e. the position of Table Mountain (and other mountain ranges) and the Atlantic Sea (coastline) means that the majority of the population lives to the east of the CBD, with very few residential opportunities available to the west. As such, there are a limited number of road-based routes to access and exit the City's Central CBD, to and from these east-lying areas which results in significant peak period congestion issues on the City's road network. In fact, results from a study undertaken by GPS manufacturer Tomtom (2014) show that the Cape Town road network is the most congested in the country. It is anticipated that the above-mentioned conditions make it attractive/possible for vehicles leaving the CBD during the PM peak period to rat-run through the immediately adjacent suburban areas, in an attempt to bypass the excessive levels of congestion currently experienced on the major routes. This practice creates major health, safety and economic problems for the affected communities and is a cause for major unhappiness as a result of the associated deterioration in their overall quality of life.